Triazolopyrimidines Are Microtubule-Stabilizing Agents that Bind the Vinca Inhibitor Site of Tubulin. Issue 6 (22nd June 2017) - Sáez-Calvo, Gonzalo; Sharma, Ashwani; Balaguer, Francisco de Asís; Barasoain, Isabel; Rodríguez-Salarichs, Javier; Olieric, Natacha; Muñoz-Hernández, Hugo; Berbís, Manuel Álvaro; Wendeborn, Sebastian; Peñalva, Miguel Angel; Matesanz, Ruth; Canales, Ángeles; et al.
Summary: Microtubule-targeting agents (MTAs) are some of the clinically most successful anti-cancer drugs. Unfortunately, instances of multidrug resistances to MTA have been reported, which highlights the need for developing MTAs with different mechanistic properties. One less explored class of MTAs are [1, 2, 4]triazolo[1, 5-a]pyrimidines (TPs). These cytotoxic compounds are microtubule-stabilizing agents that inexplicably bind to vinblastine binding site on tubulin, which is typically targeted by microtubule-destabilizing agents. Here we used cellular, biochemical, and structural biology approaches to address this apparent discrepancy. Our results establish TPs as vinca-site microtubule-stabilizing agents that promote longitudinal tubulin contacts in microtubules, in contrast to classical microtubule-stabilizing agents that primarily promote lateral contacts. Additionally we observe that TPs studied here are not affected by p-glycoprotein overexpression, and suggest that TPs are promising ligands against multidrug-resistant cancer cells. Graphical Abstract: Highlights: Triazolopyrimidines are microtubule stabilizers targeting the tubulin vinca site Triazolopyrimidines stabilize longitudinal tubulin contacts Triazolopyrimidines are not affected by p-glycoprotein overexpression Abstract : Sáez-Calvo et al. describe a family of microtubule-stabilizing agents (MSAs) with a new mechanism of action: Instead of stabilizing lateral contacts between tubulin subunits in microtubules, as MSAs typically do, they stabilize longitudinal contacts by binding to the vinca-site normally targeted by classical microtubule-destabilizing agents such as vinblastine and eribulin.